2021
DOI: 10.1016/j.surg.2021.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Fascial closure in giant ventral hernias after preoperative botulinum toxin a and progressive pneumoperitoneum: A systematic review and meta-analysis

Abstract: Background: The primary objective was to assess the perioperative efficacy of the preoperative use of progressive pneumoperitoneum or Botulinum Toxin A injections in ventral hernia repair. Methods: Embase, Medline Ovid, Web of Science, Cochrane Central, and Google Scholar were systematically searched. Studies in English reporting on fascial closure, indications, complications or postoperative outcomes in adult patients that had undergone progressive pneumoperitoneum, Botulinum Toxin A injections, or both befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A number of groups have described potential indications for BTX which range from specific hernia characteristics such as defect width, to less specific criteria driven by expert opinion or multi-disciplinary team meetings. A systematic review by van Rooijen et al (12) concluded that whilst certain given indications for PPP were fairly definitive (e.g., loss of domain more than 20%), indications for BTX were less so.…”
Section: Indications and Use With Pppmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of groups have described potential indications for BTX which range from specific hernia characteristics such as defect width, to less specific criteria driven by expert opinion or multi-disciplinary team meetings. A systematic review by van Rooijen et al (12) concluded that whilst certain given indications for PPP were fairly definitive (e.g., loss of domain more than 20%), indications for BTX were less so.…”
Section: Indications and Use With Pppmentioning
confidence: 99%
“…Similarly, when Deerenberg produced a prospective study of 108 patients from the Carolinas Medical Centre, the decision to use BTX was based on opinion and discussion among expert hernia surgeons (14). Others have identified further qualitative CT findings such as shortened or thickened lateral abdominal muscles (12).…”
Section: Indications and Use With Pppmentioning
confidence: 99%
See 3 more Smart Citations